Developing an annual training program for the mixed martial arts athlete - Huldi, F. J.; Cisar, C. J. (Strength and Conditioning Journal, 2023)
Mixed martial arts (MMA) is a multidimensional combat sport combining various forms of grappling and striking methodologies. The sport challenges the strength and conditioning professional because of the conflicting metabolic demands, high degree of variability, and a lack of a fixed competitive schedule. The existing literature identifies the need for highly developed neuromuscular qualities and high aerobic and anaerobic capacities. Although previous research has identified the physiological profile of a high-level MMA athlete, there is limited peer-reviewed research identifying the most optimal periodization strategy to improve performance. Furthermore, there seems to be no existing literature investigating the implementation of velocity-based training (VBT). This training methodology uses movement velocity to assign training loads to mitigate fatigue and improve strength and power adaptations. Existing literature on VBT suggests that it is a superior method of assigning training load compared with traditional percentage-based training. Therefore, this article serves to identify the physiological profile of the MMA athlete, outline VBT, and provide a guideline for designing an MMA strength and conditioning program to optimize performance using VBT.